Analisis Pengaruh Hukuman Mati Pekerja Migran Indonesia terhadap Hubungan Bilateral Indonesia dan Arab Saudi 2010-2018 - Sani, Eprida; Pattipeilohy, Shary Charlotte Henriette (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The pattern of bilateral relations between Indonesia and Saudi Arabia continues to run well even though many Indonesian migrant workers stumble over death penalty cases even to the death sentence without notification by the Saudi government. This paper aims to answer the question why the Indonesian government continues to establish good relations with Saudi Arabia after the death sentence of the PMI. To answer this question, the author use the concept of national interest from the theory of realism that was stated by K.J. Holsti (1996) where a country continues to cooperate with other countries due to its vital interests (Core Values), the medium term (Middle-range Objectives), and the long-term (Long-range goals) over other countries. The results of this study found that the cause of Indonesia to maintain bilateral relations with Saudi Arabia was to achieve national interests that were prioritized. In the interests of vital nature, Indonesia has a great responsibility to comply with the needs of the Hajj and Umrah of its citizens where this worship is carried out in the city of Mecca, located in Saudi Arabia. Then, in the medium term interests, Saudi Arabia is still one of the partners in cooperation which is the main destination country for sending PMIs. In addition to reducing unemployment, the existence of PMI contributes to the Indonesian economy through PMI remittances. Finally, in the longterm interests, both Indonesia and Saudi have a commitment to create international peace and security through Islamic cooperation organizations (OIC).